LE FORT I OSTEOTOMY AS A SURGICAL APPROACH TO REMOVE A JUVENILE OSSIFYING FIBROMA IN THE MAXILLARY SINUS: PEDIATRIC CASE REPORT - Nogueira, Mateus Ferreira; Jesus, Oliver Renê Viana de; Nogueira , Maysa Ferreira; Albuquerque , Maria Carolina Cabral de; Oliveira , Mateus Ferreira; Donato, Luis Philippe Lopes; Nogueira, Pedro Thalles Bernardo de Carvalho (Brazilian Journal of Implantology and Health Sciences, 2024)
Ossifying fibroma (OF) is a well-defined benign neoplasm formed by different fibrocellular tissue and mineralized material. The OF clinical presentation is commonly an asymptomatic slow-growing swelling, mainly affecting the posterior mandibular region. Radiographically, this condition is characterized as a well-defined lesion with radiopaque and radiolucent areas. Histopathology shows dense cellular fibrous stroma and characteristic spheroidal calcifications called psammoma bodies. Regarding pediatric patients, the Juvenile Ossifying Fibroma (JOF) is an uncommon benign fibro‑osseous lesion with fast growth that impacts the facial skeleton, as it has a high-frequency potential. It occurs in early life, and approximately 79% are diagnosed before the age of 15 years. It affects both genders equally, and the maxilla is more involved compared to the mandible, there are cases also discovered in the orbit and skull. Surgical intervention to remove the tumor is the treatment of choice. The article presents a case of a pediatric patient who had the diagnosis of Juvenile Ossifying Fibroma and was submitted to surgical removal. The Le-Fort I Osteotomy approach proved to be safe, as it allows direct access to the base of the skull, allows good visualization and tumor exposure, and also allows easy tumor manipulation and curettage, enabling the preservation of facial aesthetics.